Intrastromal corneal ring segment implantation in pediatric patients with keratoconus: long-term follow-up (Ukrainian Journal of Ophthalmology, 2023)
Purpose: To evaluate the long-term outcomes of Intrastromal Corneal Ring Segments (ICRS) implantation in pediatric patients with keratoconus. Methods: Retrospective analysis of eyes with ICRS implantation in pediatric age. Uncorrected (UCVA) and best-corrected (BCVA) visual acuity, maximum and minimum keratometry (Kmax and Kmin), and corneal thickness at the thinnest point (CTTP) were evaluated preoperatively, 6 to 12 months after surgery, 5 years after surgery, and at the last follow-up visit (>10 years after surgery). Results: Fourteen eyes (10 patients) were included. In 5 eyes all ICRS were explanted and in 1 eye, one of the segments was explanted. UCVA (p=0.028) and BCVA (p=0.028) improved 6 to 12 months after surgery and remained stable afterwards (p>0.999). There was a decrease in Kmax and Kmin 6 to 12 months after surgery (p0.999) but there was an increase in Kmin (p=0.028). There were no changes in CTTP (p=0.097).Conclusion: ICRS implantation seems to be a minimally invasive, and reversible procedure that leads to improvement of BCVA and keratometry readings.  Despite this, the need for explantation increased overtime.
Keywords: Keratoconus; Intrastromal corneal ring segments; visual acuity; keratometry